2016
DOI: 10.7307/ptt.v28i2.1726
|View full text |Cite
|
Sign up to set email alerts
|

Factors of Perceived Waiting Time and Implications on Passengers’ Satisfaction with Waiting Time

Abstract: In order to explore the influence factors on perceived waiting time, a multiple linear regression model has been used to quantitatively describe the relationship between perceived waiting time and various factors. The model is established with 234 data, which is surveyed with questionnaire at three stops in Harbin, China. The results show that several certain factors (“trip purpose - where to”, “presence of a companion - whether one has a companion or not”, “having a timing device - whether one has a timing de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Psarros et al (2011) estimated that patrons traveling for work purposes overestimate their wait times by a factor of about 1.3 [10]. Feng et al (2015) showed that the trip purpose is a significant predictor of perceived wait time [11]. The findings in this study followed the conclusions of Psarros et al (2011) in that passengers traveling for work purposes overestimated their waiting time the most.…”
Section: Trip Purposesupporting
confidence: 83%
See 2 more Smart Citations
“…Psarros et al (2011) estimated that patrons traveling for work purposes overestimate their wait times by a factor of about 1.3 [10]. Feng et al (2015) showed that the trip purpose is a significant predictor of perceived wait time [11]. The findings in this study followed the conclusions of Psarros et al (2011) in that passengers traveling for work purposes overestimated their waiting time the most.…”
Section: Trip Purposesupporting
confidence: 83%
“…The anxiety of getting to work on time during the morning explained the high morning period ratio [10]. Another study conducted in China also revealed that the period of day is a significant predictor of waiting time [11].…”
Section: Period Of Daymentioning
confidence: 95%
See 1 more Smart Citation
“…9 A study showed that trip purpose is a significant predictor of perceived wait time, also finding that passengers traveling for work purposes overestimated their waiting time the most. 19…”
Section: Trip Purposementioning
confidence: 99%
“…In order to achieve harmonized (planned) vehicle arrival i.e. macroscopic traffic flow harmonization into ferry ports followed by instant vehicle boarding aboard ferry optimization concept encompassed in FQMS relies on the principle of providing certain group of usersentities -vehicles privilege for priority ferry boardinggrant such vehicles right for immediate ferry boarding upon their arrival into ferry port, therefore minimizing vehicle(s) waiting time as one of the most important factors on passengers' satisfaction [10].…”
Section: Introductionmentioning
confidence: 99%